The Effect of Humic Substances and Phosphate Fertilizer on Growth and Nutrient Uptake of the Potato - Martins, Jéssyca D. L. [UNESP]; Soratto, Rogério P. [UNESP]; Fernandes, Adalton M. [UNESP] (Taylor & Francis, 2020)
The use of applied phosphorus (P) and the uptake of nutrients from the soil by plants can be improved when the fertilizer is combined with the application of humic substances (HS). However, these beneficial effects are inconsistent and can depend on the type of soil. This study was performed to evaluate the effects of the application of HS (0, 1.25, and 7.50 mL pot–1), as Humic HF®, and fertilizer-P (10, 50, 100, and 200 mg P dm–3), as triple superphosphate, on root morphological characteristics, dry matter accumulation, nutrient uptake, and tuber yield of potatoes grown in sandy and clayey soils. Only under low P supply in the sandy soil did the supply of HS, at the rate of 1.25 mL pot–1, increase the plant growth, yield of tubers, and uptake of macronutrients by the plants, without affecting the efficiency of the P fertilization. In the clayey soil, which had a higher organic matter content, the application of HS did not affect plant growth, tuber yield or nutrient uptake. In both soils, P fertilization increased plant growth, tuber yield, and nutrient uptake. The combined application of HS and P increased the root length of potatoes in sandy soil.
Keywords: clayey soil; humic acids; mineral nutrition; sandy soil; Solanum tuberosum